The petes go marching ebook - Dean, James (Pete the Cat., 2018)
#1 New York Times bestseller James Dean puts a groovy spin to the classic children's song "The Ants Go Marching" with everyone's favorite cool cat. Join Pete the Cat as he rocks out to this classic tune with a supercool twist in this paper-over-board picture book. Your child, or even your classroom of children, is sure to want to march along with Pete, 1, 2, 3!